2009
DOI: 10.1007/s00412-009-0213-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinct acetylation of Trypanosoma cruzi histone H4 during cell cycle, parasite differentiation, and after DNA damage

Abstract: Histones of trypanosomes are quite divergent when compared to histones of most eukaryotes. Nevertheless, the histone H4 of Trypanosoma cruzi, the protozoan that causes Chagas' disease, is acetylated in the N terminus at lysines 4, 10, and 14. Here, we investigated the cellular distribution of histone H4 containing each one of these posttranslational modifications by using specific antibodies. Histone H4 acetylated at lysine 4 (H4-K4ac) is found in the entire nuclear space preferentially at dense chromatin regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 54 publications
2
32
0
2
Order By: Relevance
“…In this work, treatment with topo I inhibitors promoted severe unpacking of the heterochromatin in interphase cells, which is usually observed surrounding the nucleolus and juxtaposed to the inner nuclear membrane [7,54]. Such ultrastructural alterations were also observed in T. cruzi epimastigotes exposed to ␥ radiation [55]. Taken together, the effects of topo I inhibitors on growth impairment and nuclear structure alterations suggest that the T. cruzi cell cycle was arrested in order to repair the DNA.…”
Section: Discussionmentioning
confidence: 74%
“…In this work, treatment with topo I inhibitors promoted severe unpacking of the heterochromatin in interphase cells, which is usually observed surrounding the nucleolus and juxtaposed to the inner nuclear membrane [7,54]. Such ultrastructural alterations were also observed in T. cruzi epimastigotes exposed to ␥ radiation [55]. Taken together, the effects of topo I inhibitors on growth impairment and nuclear structure alterations suggest that the T. cruzi cell cycle was arrested in order to repair the DNA.…”
Section: Discussionmentioning
confidence: 74%
“…We, along with others, have already shown that it is possible to synchronize T. cruzi epimastigote cells with hydroxyurea. 9,17,18 Hydroxyurea inhibits the nucleotide reductase enzyme, thereby consuming dNTPs. In the absence of dNTPs, DNA elongation is blocked and most of the cells are arrested very early in S phase.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that 18 h after the release, most of the cells are still at G 2 . 18 To examine cells just after mitosis, we took epimastigotes 20 h after hydroxyurea release. At this point, 25% of the cells were in cytokinesis (two nuclei, two kinetoplasts and two flagella) and 75% of cells had concluded the different patterns of tcorc1/cdc6 and tcpcna localization are related to the cell cycle.…”
Section: Resultsmentioning
confidence: 99%
“…They have been implicated in trypanosome transcription initiation and termination (154,162,174,191), cell cycle progression (70,85), and telomeric silencing (90). Acetylated histone H4 is distributed in a punctate pattern in the T. brucei and T. cruzi nucleoplasm (133,162,165). In the case of H4K10ac, this most likely reflects the association with pol II transcription start sites (162).…”
Section: Trypanosome Chromatinmentioning
confidence: 99%